Lead(II) complexes of 1-alkyl-2-(arylazo)imidazole: Synthesis, structure, photochromism and metallomesogenic properties. (15th October 2016) - Mallick, Debashis; Panda, Uttam; Jana, Srikanta; Sen, Chandana; Mondal, Tapan Kumar; Sinha, Chittaranjan
Graphical abstract: Upon light irradiation the coordinated 1-alkyl-2-(arylazo)imidazole (Raai-C n H2 n +1 ) shows E-to-Z ( trans -to- cis ) isomerisation about the –NN– bond and the reverse transformation, Z-to-E ( cis -to- trans ), is achieved by thermal treatment. The rate, quantum yield, activation energy and entropy of activation are controlled by the chain length, –C n H2 n +1 . [Pb(Meaai-C16 H33 )(μ-I)4 ] n (4b ) shows a metallomesogenic property in the cooling cycle. The structures of the complexes have been supported by single crystal and other spectroscopic data. Abstract: The reaction between PbI2 and 1-alkyl-2-(arylazo)imidazole (Raai-C n H2 n +1, R = H, Me and n  = 10, 12, 14, 16, 18, 20, 22) has synthesized the iodo bridging complexes [Pb(Raai-C n H2 n +1 )(μ-I)4 ] n . These complexes were characterized by spectroscopic data and the structure has been confirmed in the case of [Pb(Meaai-C16 H33 )(μ-I)4 ] n by single crystal X-ray diffraction measurements. The complexes show E-to-Z ( trans -to- cis ) isomerisation of the coordinated Raai-C n H2 n +1 ligand in DMF solution upon UV light irradiation. The reverse transformation, Z-to-E ( cis -to- trans ), is very slow with visible light irradiation and has been carried out by increasing the temperature. The quantum yield ( ϕ E→Z ) and rate of E-to-Z isomerisation of [Pb(Raai-C n H2 n +1 )(μ-I)4 ] n are lower than those of the free ligand. The activation energy ( E a ) of the Z-to-E isomerisation increases and the activation entropy (Δ S ∗ ) decreases with the chain length, –C n H2 n +1, in the coordinated ligand. [Pb(Meaai-C16 H33 )(μ-I)4 ] n (4b ) shows metallomesogenic properties on cooling and undergoes phase transitions I (80.7 °C)–SmC (69.8 °C)– Cr (58.5 °C).